2009
DOI: 10.1203/pdr.0b013e3181b1bc19
|View full text |Cite
|
Sign up to set email alerts
|

Siglec-9 and SHP-1 Are Differentially Expressed in Neonatal and Adult Neutrophils

Abstract: Neonatal PMN (polymorphonuclear neutrophils) exhibit altered inflammatory responsiveness and greater longevity compared with adult PMN; however, the involved mechanisms are incompletely defined. Receptors containing immunoreceptor tyrosine-based inhibitory motif (ITIM) domains promote apoptosis by activating inhibitory phosphatases, such as Src homology domain 2-containing tyrosine phosphatase-1 (SHP-1), that block survival signals. Sialic acid-binding immunoglobulin-like lectin (Siglec)-9, an immune inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
(64 reference statements)
4
18
0
Order By: Relevance
“…Thus, the heightened expression of IL-8 in neonatal neutrophils may be related to alterations in regulatory signaling pathways. We recently reported prominent Akt-mediated survival signaling [42] and have observed a unique pattern of NF-B-regulated function in neonatal neutrophils (manuscript in preparation). In contrast to the pattern of IL-8 secretion, surviving neutrophils released negligible amounts of other inflammatory cytokines, including IL-1 ␣ , IL-1 ␀ , IL-6 and TNF-␣ .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the heightened expression of IL-8 in neonatal neutrophils may be related to alterations in regulatory signaling pathways. We recently reported prominent Akt-mediated survival signaling [42] and have observed a unique pattern of NF-B-regulated function in neonatal neutrophils (manuscript in preparation). In contrast to the pattern of IL-8 secretion, surviving neutrophils released negligible amounts of other inflammatory cytokines, including IL-1 ␣ , IL-1 ␀ , IL-6 and TNF-␣ .…”
Section: Discussionmentioning
confidence: 99%
“…19, 22 Similarly, Siglec-9-induced neutrophil cell death is caspase and ROS-dependent in resting cells but only ROS-dependent in activated cells. 23 However, Siglec-9 and Siglec-E also have ITIM/SHP-1/inhibitory signaling related functions in that both are constitutively associated with SHP-1 24, 25 and Siglec-E-deficient mice exhibit enhanced neutrophil recruitment in endotoxin-induced acute pulmonary inflammation. 25 Intriguingly, Siglec-8 signaling and function in a different cell type, namely mast cells, is distinct from that in eosinophils and involves inhibition of mast cell FcΔRI-mediated activation and function rather than cell death.…”
Section: Expression Patterns Ligands and Cellular Functions Of Selecmentioning
confidence: 99%
“…They found that the prolonged survival of neonatal neutrophils was due to less abundant sialic acid-binding immunoglobin-like lectin-9 (Siglec-9) and Src homology domain-2 containing tyrosine phosphatase-1 (SHP-1), two pro-apoptotic proteins. Rashmi suggested that diminished SHP-1 function in neonatal neutrophils can explain the high basal phosphorylation of LYN previously reported by Yan et al [47]. Marodi et al investigated a third intracellular signaling pathway, the STAT family of proteins, using neonatal monocytes.…”
Section: Granulopoiesis In Neonatesmentioning
confidence: 99%
“…Pretreatment of cord blood neutrophils with anti-Fas antibodies induced significantly less apoptosis (24% v. 63%) than seen in adult neutrophils [110]. The limited responsiveness to apopototic stimuli is related to decreased surface receptor expression of the Fas receptor, decreased pro-apoptotic intracellular signaling molecule caspase-3, and decreased activity of the pro-apoptotic proteins Siglec-9 and SHP-1[47, 111, 112]. Adult and neonatal cells were thought to be equally responsive to anti-apoptotic factors including GM-CSF, IFN-Îł, and LPS [111].…”
Section: Qualitative Insufficiency Of Neonatal Neutrophilsmentioning
confidence: 99%